The Role of Fiqh Education in Preparing Students for Marriage (A Case Study at STDI Imam Syafi'i Jember): Peran Edukasi Ilmu Fikih dalam Mempersiapkan Mahasiswa untuk Menikah (Studi Kasus di STDI Imam Syafi'i Jember) - Rahmatullah Ramdani; Kazhimi Abdillah; David Sanjaya; Muhamad Ilyas; Mochammad Nasir (Al-Zaujiyyah: Jurnal Hukum Keluarga Islam, 2025)
Education in Islamic jurisprudence is a crucial process in understanding the laws of Islam, including those related to marriage. Marriage readiness is an essential condition, encompassing the physical, mental, psychological, and material maturity of individuals, enabling the formation of a healthy marital relationship capable of fulfilling the developmental responsibilities within marriage. Sekolah Tinggi Dirasat Islamiyah (STDI) Imam Syafi'i Jember is a private higher education institution located in Jember Regency. The aim of this research is to analyze and discover the concept of Islamic jurisprudence in matters of marriage, education in Islamic jurisprudence, and its implications on marriage readiness. A qualitative approach with a case study research type is employed. The results of this research indicate that (1) there are several concepts of Islamic jurisprudence in marriage, such as the encouragement to marry, the conditions for a valid marriage, partner criteria, the issue of the dowry, and the rights and obligations of partners, (2) Students at STDI Imam Syafi'i Jember need to understand the importance of Islamic jurisprudence in marriage, learn its fundamentals within the campus environment, and continually enhance their knowledge through various sources like books, seminars, study groups, websites, and videos, (3) The implications for STDI Imam Syafi'i Jember students regarding marriage readiness involve ensuring self-preparedness, preparing to address post-marriage challenges, building strong mental resilience, selecting a partner in accordance with Islamic principles, and being prepared to establish a harmonious family.